2022
DOI: 10.3390/ijerph19010523
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Use of Antidepressants for Adolescents with Depression/Anxiety Who Regularly Use Cannabis: A Narrative Review

Abstract: Depression and anxiety disorders are two of the most common and growing mental health concerns in adolescents. Consequently, antidepressant medication (AD) use has increased widely during the last decades. Several classes of antidepressants are used mainly to treat depression, anxiety, and obsessive-compulsive disorders by targeting relevant brain neurochemical pathways. Almost all randomized clinical trials of antidepressants examined patients with no concomitant medications or drugs. This does not address th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 238 publications
(268 reference statements)
0
4
0
1
Order By: Relevance
“…Em testes realizados pelo estudo experimental laboratorial com adultos saudáveis realizado na Escócia, onde foi realizado o Teste de Estresse Agudo de Maastricht (MAST), com o fito de induzir estado de ansiedade nos pacientes; esse teste possui duas fases sendo uma onde o procedimento é explicado durante 5 minutos e a outra leva cerca de 10 minutos induzindo o estresse agudo (Shoval et al, 2022).…”
Section: Resultado E Discussãounclassified
“…Em testes realizados pelo estudo experimental laboratorial com adultos saudáveis realizado na Escócia, onde foi realizado o Teste de Estresse Agudo de Maastricht (MAST), com o fito de induzir estado de ansiedade nos pacientes; esse teste possui duas fases sendo uma onde o procedimento é explicado durante 5 minutos e a outra leva cerca de 10 minutos induzindo o estresse agudo (Shoval et al, 2022).…”
Section: Resultado E Discussãounclassified
“…Many advances have been made in mood disorder treatment over the past decades. Approximately 30% of the population does not respond to current therapies, and the search for novel pharmacological approaches continues [ 178 , 179 ].…”
Section: Endocannabinoid System Emerging As a Pharmacotherapy Target ...mentioning
confidence: 99%
“…However, symptoms such as paranoia, irritation, dysphoria, depression, depersonalization, and demotivation may appear in some individuals with such adverse effects [ 51 , 180 ]. The reactions depend on the patient’s endocannabinoid activity, the dose used (normally stimulating action at a low dose and inhibitory action at a high dose), the proportion of phytocannabinoids, and the terpenoid composition [ 179 , 181 ]. Evidence is increasing regarding the role of eCB in mood regulation.…”
Section: Endocannabinoid System Emerging As a Pharmacotherapy Target ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Cannabis use is also associated with poor treatment outcomes among youth with comorbid mental health disorders. For example, a recent narrative review found that adolescents with depression and anxiety who used cannabis frequently showed a loss of effectiveness of antidepressants ( Hen-Shoval et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%